Measuring Public Sentiment on Electric Cars in Indonesia: A Social Media Data Analysis - Michael Michael; Melissa Indah Fianty (Universitas Islam Raden Rahmat, Malang, 2024)
The Industry 4.0 era has driven rapid growth in Indonesia's automotive industry, with increasing environmental awareness fueling demand for eco-friendly vehicles, such as electric cars. In 2023, electric car sales surged by 65%, reaching 17.06 thousand units. However, widespread adoption remains hindered by high costs and limited charging infrastructure. This study aims to analyze Indonesian public sentiment toward electric cars using the Naïve Bayes algorithm. The analysis shows that positive sentiment is dominant, reflecting broad support for this innovation, despite concerns over cost and infrastructure. The Naïve Bayes model achieved an accuracy of 80%, with a precision of 84%, recall of 90%, and an F1-score of 87%. These findings can help the industry devise more effective marketing and educational strategies to encourage the adoption of electric vehicles in Indonesia.